The Communication Approach Employed By The Coach and Students In Training and Developing The Potential of Student Basketball Athletes at DBL Academy Basketball - Bram Putra Pratama (LPPM Stikosa-AWS, 2023)
In life, humans are often brought together in a container or organization, either formal or non-formal. In a sports club institution that has many students, an effective way is needed for a coach in the process of developing children's talents by communicating well. To find out how the patterns and processes of communication between coaches and students in the process of developing the potential of basketball student athletes at DBL Academy, researchers conducted descriptive qualitative research, using Bandura's social learning theory which has a starting point that humans learn through observation and Devito's theory of interpersonal communication patterns. The researcher concluded that DBL Academy offers a series of programs that are not only focused on basketball but also on teaching and training life values to be reflected in the realization of developing student athlete potential. In addition, the researcher concluded that DBL Academy uses interpersonal communication patterns, including intimate communication carried out with people who already have emotional closeness, social conversations that are not so deep but are fun for the perpetrator, interrogation which is communication that demands information from the interlocutor, and interviews. Like communication patterns that are implemented in all educational institutions.